An Improved SHEPWM Modulation Algorithm for Three-levelEnergy Feedback Inverter - WU Xuefeng; CHEN Jielian; WANG Xiong; SONG Qianru; YIN Weiheng (Kongzhi Yu Xinxi Jishu)
The maximum switching frequency of high power converters is limited by the heat dissipation system and cannot be randomly increased. Consequently, increasing low-order harmonics are introduced into the grid. In order to better suppress harmonics and improve the quality of grid-connected power, an improved SHEPWM modulation method is proposed to be applied to the three-level inverter based on the in-depth analysis of the traditional selected harmonic elimination algorithm. Not only maintaining the advantages of the traditional SHEPWM modulation algorithm, the proposed method also avoids the increase of high-order harmonics which can not be achieved by the traditional SHEPWM modulation algorithm. Meanwhile, the mathematical model of selected harmonic elimination is optimized and genetic algorithm is employed to solve the harmonic elimination model of the three-level NPC inverter. Compared to the traditional Newton iteration method, the genetic algorithm adopted in this paper needn’t consider the initial value of the switching angles. Finally, the method is simulated on Matlab/Simulink platform, and compared with the traditional SHEPWM algorithm based on Newton iteration algorithm. The results verify the effectiveness of the proposed method.